Pengaruh Struktur Aktiva, Current Ratio, Risiko Bisnis, dan Pertumbuhan Penjualan Terhadap Struktur Modal: (Studi Empiris Pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Rolanda, Ivo; Novita Jasmani, Damai (Jurnal Disrupsi Bisnis, 2024)
The average capital structure of food and beverage companies listed on the Indonesia Stock Exchange during the period 2018-2022 experienced fluctuating changes annually. This study aims to determine the influence of asset structure, current ratio, business risk, and sales growth on the capital structure. The research employs a quantitative research method and utilizes secondary data in the form of financial reports from 2018-2022 of food and beverage subsector companies listed on the Indonesia Stock Exchange. The population consists of 20 companies from the Indonesia Stock Exchange. Sampling in this study includes 16 companies using purposive sampling technique. The analytical tool used is multiple linear regression tested using Statistical Product and Service Solution (SPSS) version 26. The results of this research indicate that the current ratio significantly influences the capital structure, while asset structure, business risk, and sales growth do not significantly affect the capital structure